Vortex‐dislodged cells from bone marrow trephine biopsy yield satisfactory results for flow cytometric immunophenotyping. (24th June 2016) - Bommannan, K.; Sachdeva, M. U. S.; Gupta, M.; Bose, P.; Kumar, N.; Sharma, P.; Naseem, S.; Ahluwalia, J.; Das, R.; Varma, N.
Summary: Introduction: A good bone marrow (BM) sample is essential in evaluating many hematologic disorders. An unsuccessful BM aspiration (BMA) procedure precludes a successful flow cytometric immunophenotyping (FCI) in most hematologic malignancies. Apart from FCI, most ancillary diagnostic techniques in hematology are less informative. We describe the feasibility of FCI in vortex‐dislodged cell preparation obtained from unfixed trephine biopsy (TB) specimens. Methods: In pancytopenic patients and dry tap cases, routine diagnostic BMA and TB samples were complemented by additional trephine biopsies. These supplementary cores were immediately transferred into sterile tubes filled with phosphate‐buffered saline, vortexed, and centrifuged. The cell pellet obtained was used for flow cytometric immunophenotyping. Results: Of 7955 BMAs performed in 42 months, 34 dry tap cases were eligible for the study. Vortexing rendered a cell pellet in 94% of the cases (32 of 34), and FCI rendered a rapid diagnosis in 100% of the cases (32 of 32) where cell pellets were available. Conclusion: We describe an efficient procedure which could be effectively utilized in resource‐limited centers and reduce the frequency of repeat BMA procedures.